"Klobuk dr. Kreka" - Kardoš, Štefan (Slavistična revija, 1996)
Dr. Janez Evangelist Krek is a figure who had a profound impact on Slovene politics and culture at the turn of the 19th century. It is possible to imagine his work not touching one way or another upon the life and work of Ivan Cankar, the main figure of slovene New Romanticism that was on the rise at the time.
Keywords: 19./20.st.; Cankar, Ivan, 1876-1918; Krek, Janez Evangelist, 1865-1917; literarne študije; literarni vplivi; moderna; Moderna Therapeutics; Slovene literature; slovenska književnost